MODERN FAMILY, ITS TYPES AND FUNCTIONS - Matnazarova Dilorom Radjabbaevna (Modern American Journals, 2025)
This article examines the types of modern families, their role in society, and their main functions from a sociological and ethnographic perspective. The family is considered not only as a biological and economic unit, but also as an important social institution that performs educational, communicative, and pheliocytological functions. The article analyzes the criteria for classifying family types and the importance of each function in modern conditions based on scientific literature. The relevance of the policy of attention and support for the family by the state and society is also emphasized.
Keywords: Family, modern family, sociology, functions, social institution, upbringing, communication, pheliocytology, demography, society.